Fiber delivery and diagnostics of laser spark ignition for natural gas engines - Joshi, Sachin, author; Yalin, Azer, advisor; Willson, Bryan, advisor (Colorado State University. Libraries, 2008)
Laser ignition via fiber optic delivery is challenging because of the need to deliver pulsed laser beam with relatively high energy and sufficient beam quality to refocus the light to the intensity required for creating spark. This dissertation presents work undertaken towards the development of a multiplexed fiber delivered laser ignition system for advanced lean-burn natural gas engines. It also describes the use of laser ignition system to perform in-cylinder optical diagnostics in gas engines. Key elements of the dissertation includes: (i) time resolved emission spectroscopy (TRES) of laser sparks in air to investigate the dependence of spark temperatures and electron number densities on ambient gas pressures, (ii) optical characterization of hollow core fibers, step-index silica fibers, photonic crystal fibers (PCFs) and fiber lasers, (iii) development and on-engine demonstration of a multiplexer to deliver the laser beam from a single laser source to two engine cylinders via optical fibers, and (iv) demonstration of simultaneous use of laser sparks for ignition and Laser Induced Breakdown Spectroscopy (LIBS) to measure in-cylinder equivalence ratios in a Cooperative Fuel Research (CFR) engine. For TRES of laser sparks, the ambient gas pressure is varied from 0.85 bar to 48.3 bar (high pressures to simulate elevated motored in-cylinder pressures at time of ignition in advanced gas engines). At later stages (~1μs) of spark evolution, spark temperatures become comparable at all pressures. Electron number densities increase initially with increasing ambient gas pressure but become comparable at pressures greater than ~20 bar. The effects of launch conditions and bending for 2-m long hollow core fibers are studied and an optimum launch f/# of ~55 is shown to form spark in atmospheric pressure air. Spark formation using the output of a pulsed fiber laser is shown and delivery of 0.55 mJ nanosecond pulses through PCFs is achieved. Successful multiplexed laser ignition of a CAT G3516C gas engine via hollow core fibers is shown. LIBS analysis conducted at equivalence ratios from 0.6 to 0.95 in the CFR engine show a linear variation and linear correlation (R2 > 0.99) of line intensity ratio (Hα/O777 and Hα/Ntot) with equivalence ratio.
Keywords: engines; equivalence ratios; fiber optics; laser ignition; laser-induced breakdown spectroscopy; natural gas; mechanical engineering; optics; plasma physics